2002
DOI: 10.1161/01.cir.0000038500.43292.d7
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Level Reduction by the 3-Hydroxy-3-Methylglutaryl Coenzyme-A Inhibitor Simvastatin Is Accompanied by a Related Reduction of F 2 -Isoprostane Formation in Hypercholesterolemic Subjects

Abstract: Background-Both statins and vitamin E, by reducing the rate of lipid peroxidation, may interfere with oxidative stress, but the impact of their combination is unknown. Methods and Results-We randomized 43 hypercholesterolemic patients (21 men, 22 women, age 63Ϯ11 years) to either simvastatin, to achieve Ͼ20% reduction of total cholesterol, or simvastatin plus 600 mg/d vitamin E for 2 months. Patients were then crossed over to the alternative treatment. Lipid parameters documented patients' compliance to simvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 48 publications
6
61
0
2
Order By: Relevance
“…21,22 A reduction of urinary isoprostanes or an increase of circulating vitamin E has been observed after short-term (3 days) or long-term treatment with statins. [23][24][25] In the present study, using 2 markers of oxidative stress, ie, urinary isoprostanes and sNOX2-dp, we demonstrated that high-dose atorvastatin acutely decreases both markers, indicating that it exerts a rapid antioxidant effect. The parallel decrease of Nox2 activity and urinary isoprostanes reinforces data from previous studies suggesting a major role for Nox2 in the production of isoprostanes.…”
Section: Antioxidant Effect By Statinssupporting
confidence: 55%
“…21,22 A reduction of urinary isoprostanes or an increase of circulating vitamin E has been observed after short-term (3 days) or long-term treatment with statins. [23][24][25] In the present study, using 2 markers of oxidative stress, ie, urinary isoprostanes and sNOX2-dp, we demonstrated that high-dose atorvastatin acutely decreases both markers, indicating that it exerts a rapid antioxidant effect. The parallel decrease of Nox2 activity and urinary isoprostanes reinforces data from previous studies suggesting a major role for Nox2 in the production of isoprostanes.…”
Section: Antioxidant Effect By Statinssupporting
confidence: 55%
“…Experimental studies revealed that statins inhibit production of superoxide via the NADPH oxidase system in monocytes, 26 neutrophils, 27 and endothelial cells, 28 because activation of NADPH oxidase is dependent on an isoprenoid group, ie, geranyl geraniol, which derives from HMG-CoA and is thus inhibited by statins. 29 In parallel to these in vitro observations, De Caterina and coworkers 30 found a significant reduction of F2-isoprostane, a product of the attack of reactive oxygen species on esterified arachidonic acid, in patients with hypercholesterolemia who were receiving simvastatin. Statin therapy also lowers systemic levels of protein-bound nitrotyrosine, a marker for formation of peroxynitrite, ie, the end product of the reaction of superoxide with nitric oxide.…”
Section: Discussionmentioning
confidence: 80%
“…This finding is of particular interest, because it has been demonstrated that intervention with statins in mildly hypercholesterolemic patients reduced oxidant burden, ie, 8-iso-PGF 2␣ and 3-nitrotyrosine formation. 20,21 However, our trial was designed as a case-control study and therefore was not intended to detect such effects. Recently, a difference in urinary 8-iso-PGF 2␣ in CHD patients with 1-vessel and multivessel disease was found.…”
Section: Discussionmentioning
confidence: 99%